PENERAPAN KEPEMIMPINAN KLINIS BAGI PERAWAT PELAKSANA DI RUMAH SAKIT - Arlis; Mazly Astuty; Harry Permana Wibowo (Jurnal Keperawatan Priority, 2023)
Clinical leadership is a process to increase patient care quality with a set of nurses' capabilities in a hospital focusing on multidiscipline of care. Implementation of clinical leadership for nurses was unusual for any hospital practitioner. How this model implements were needed as proof, and whether this can aim to determine the study was aimed to find out the effectivity of Clinical Leadership Competency Framework (CLCF) implementation for nurses. Quasy experiment design was used in this research, whereas there was no control group for 52 respondents. The instruments measuring clinical leadership were adopted and modified from the standard tools. The first measurement showed that the majority of nurses' clinical leadership was in a good category, they were 31 respondents (59,6%), and for the second measurement majority of nurses' clinical leadership was in a good category also, they were 34 respondents (65,4%). T-test dependent showed that significant difference in mean between the first measurement and the second one (p=0,001; α = 0,05). It meant that CLCF was effective in influencing the nurses' clinical leadership. CLCF implementation in a hospital was a scientific simulation that could be developed for other hospitals because clinical leadership had a strong influence on nurses' performance. Excellent nurses' performance will influence patient care quality, and it will impact people's trust in the hospital finally.